Midlife bites : anyone else falling apart or is it just me? - Mann, Jen (Ballantine Books, 2022)
"From the New York Times bestselling author of People I Want to Punch in the Throat comes a smart, funny, personal examination of what it's like to be at the crossroads of a woman's midlife crisis. Jen Mann had what appeared to be the perfect life: a successful career as a bestselling author and award-winning blogger, a devoted husband, teenage kids who weren't total jerks, and a badass minivan. So imagine her surprise when, at forty-seven years old, a midlife crisis kicked her straight in the ladybits. In an attempt to deal with the resulting range of emotions and physical changes in midlife, Jen posted a completely honest now-viral post, "Anyone Else Falling Apart Or Is It Just Me?" The response was instantaneous and overwhelming. Women from all over the country flooded the comments section, glad to see they weren't the only ones experiencing this feeling of isolation and dissatisfaction. It was the beginning of a movement. Midlife Bites encompasses these important conversations and observations, and creates a space and community for women to navigate through this major point in their lives, together, offering valuable insights and takeaways. Jen shares her own story as well as advice and wisdom from the online community she built. Please note, this is not your mother's midlife crisis. Different from the typical self-help book, Jen tackles everything that bites about midlife and nothing is off-limits with her no-nonsense approach. Subjects include: raging hormones; sex (after forty); finding your purpose; learning to make new friends (yes, even as a grown-up); moving out of your comfort zone; having conversations that count, no more small talk; and how to deal with rogue chin hairs (and other nuisances). Midlife Bites is Jen Mann's call to action. She is leading the movement to create a new space where middle-aged women can share openly and honestly with one another. This no-BS collection of essays will help start the conversation and keep it going, because as women, we all have a right to be happy, fulfilled, and to feel whole, no matter what stage of life"--